The geography of speciation in dasyurid marsupials. (13th April 2020) - García‐Navas, Vicente; Kear, Benjamin P.; Westerman, Michael
Abstract: Aim: To determine the effects of competition and divergence time on morphological dissimilarity and geographical range overlap between dasyurid species at both regional and local scales. Our hypothesis is that speciation in this group has been largely allopatric at regional scale, but involved morphological divergence at local scale through sympatric character displacement. Location: Australia, New Guinea and surrounding islands. Taxon: Dasyurid (Dasyuridae) marsupials, 67 species. Methods: Geographical range overlap was quantified using polygons representing the outer limits of species distributions. Local‐scale range overlap was quantified as the degree of co‐occurrence of two taxa across a set of ecological survey plots representing 83 sampled communities. Phylogenies were generated using a novel DNA dataset, with divergence times estimated via total‐evidence dating incorporating fossils. Morphological divergence was determined using body mass and lower molar row length as proxy traits for reconstructing niche exploitation. Results: Sister species pairs were found to be sympatric in 52% (11/21) of cases. Range overlap tended to increase with node age, which supports the hypothesis that mammalian speciation is routinely allopatric. We detected no evidence of character displacement with increasing range overlap between sister species pairs. However, a negative relationship was observed between morphological divergence in body mass and range overlap across all sampled taxa, suggesting that selection in sympatry is convergent, while divergent selection occurs in allopatry. Local‐scale co‐occurrences revealed no trace of species aversion, indicating that competition has not impacted on the spatial distribution of dasyurids. Main conclusions: Despite moderate levels of sympatry through time, our results evince low rates of spatial co‐occurrence between dasyurid species. Although this may be indicative competitive exclusion, the lack of character displacement suggests that biotic interactions have likely not acted as a dominant driver of phenotypic evolution in this radiation. We alternatively posit that abiotic factors including aridity and geographical connectivity have more feasibly propagated character convergence, and led to both niche conservatism and speciation in this ubiquitous australidelphian clade.